Versatility of subtilisin: a review on structure, characteristics, and applications - Mohd Azrin, Nur Aliyah; Mohamad Ali, Mohd Shukuri; Raja Abd Rahman, Raja Noor Zaliha; Oslan, Siti Nurbaya; Muhd Noor, Noor Dina (John Wiley & Sons, Inc., 2022)
Due to its thermostability and high pH compatibility, subtilisin is most known for its role as an additive for detergents in which it is categorized as a serine protease according to MEROPS database. Subtilisin is typically isolated from various bacterial species of the Bacillus genus such as Bacillus subtilis, B. amyloliquefaciens, B. licheniformis, and various other organisms. It is composed of 268–275 amino acid residues and is initially secreted in the precursor form, preprosubtilisin, which is composed of 29-residues signal peptide, 77-residues propeptide, and 275-residues active subtilisin. Subtilisin is known for the presence of high and low affinity calcium binding sites in its structure. Native subtilisin has general properties of thermostability, tolerance to neutral to high pH, broad specificity, and calcium-dependent stability, which contribute to the versatility of subtilisin applicability. Through protein engineering and immobilization technologies, many variants of subtilisin have been generated, which increase the applicability of subtilisin in various industries including detergent, food processing and packaging, synthesis of inhibitory peptides, therapeutic, and waste management applications.